Two decades of skeletal density decline in Pocillopora spp. corals in the Mexican Pacific Ocean: Insight into a tropical eastern Pacific acidification scenario? - Andrés López-Pérez; Omar Jiménez-Gutiérrez; Héctor Reyes-Bonilla; Rafael A. Cabral-Tena; Gerardo Leyte-Morales; Francisco Medellín-Maldonado; Orión Norzagaray-López; Cecilia Chapa-Balcorta (PLoS ONE, 2026)
Corals demonstrate vulnerability to environmental changes, exhibiting the capacity to substantially modify coral calcification. In this study, we estimated declines in the density of Pocillopora coral species in the Mexican Pacific. The samples utilized in this study encompass both recently collected corals and those stored in Mexican repositories collected in the northeastern and southern Mexican Pacific regions. Density estimates indicate a 28.6% decline in coral density over the past 23 years (−0.0227 g CaCO 3 cm -3 y -1 ) in the southern Mexican Pacific, while at the entrance to the Gulf of California, density has decreased by 15.4% over the past 20 years (−0.017 g CaCO 3 cm -3 y -1 ). A comprehensive evaluation of environmental data reveals that the observed decline in Pocillopora skeletal density in Mexican Pacific reefs is concomitant with decreases in Ω ar and pH, and an increase in ocean temperature on a substantial regional scale. When considered in conjunction with the previously documented reductions in coral growth of Pocillopora spp. skeletons in the eastern Tropical Pacific, our findings indicate a potential decline in CaCO 3 production within the region's reef systems. The results of this study underscore the significance of generating long-term series of coral growth parameters for relevant reef-building species and the carbonate system in key and representative coastal areas, particularly those that are already challenging for coral survival and reef maintenance.